1999
DOI: 10.1093/glycob/9.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of 15N from ammonium into the N-linked oligosaccharides of an immunoadhesin glycoprotein expressed in Chinese hamster ovary cells

Abstract: et al., 1994). This might be a universal and previously not described reaction in mammalian cells when exposed to nonphysiological but in cell culture commonly found concentrations of ammonium. The data presented here are of significance for glycoprotein production in mammalian cell culture, since it has been shown previously that elevated levels of UDP-activated hexosamines affect N-glycan characteristics such as branching and degree of amino sugar incorporation. In addition, our results demonstrate that isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…In fact, glucosamine supplementation appeared to decrease t-PA site occupancy, which is, perhaps, surprising given that glucosamine has been shown previously to increase specific branching glycosylation reactions in recombinant protein production in BHK cells, apparently by increasing UDP-GNAc pools (Gawlitzek et al, 1998). In another study, elevated UDP-GNAc pools, resulting from ammonium addition, failed to increase glycosylation branching for an immunoadhesin glycoprotein expressed in CHO cells (Gawlitzek et al, 1999). In another model in which variable-site occupancy was evaluated, Nyberg et al (1999) showed a correlation between increased UDP-GNAc levels and increased site occupancy for interferon-␥.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, glucosamine supplementation appeared to decrease t-PA site occupancy, which is, perhaps, surprising given that glucosamine has been shown previously to increase specific branching glycosylation reactions in recombinant protein production in BHK cells, apparently by increasing UDP-GNAc pools (Gawlitzek et al, 1998). In another study, elevated UDP-GNAc pools, resulting from ammonium addition, failed to increase glycosylation branching for an immunoadhesin glycoprotein expressed in CHO cells (Gawlitzek et al, 1999). In another model in which variable-site occupancy was evaluated, Nyberg et al (1999) showed a correlation between increased UDP-GNAc levels and increased site occupancy for interferon-␥.…”
Section: Discussionmentioning
confidence: 89%
“…These and other studies demonstrated that galactose or uridine supplementation can lead to increased levels of intracellular UDP-Gal, likely leading to increased intracellular biosynthesis of galactosylated antibodies. This increase could compensate for reduced endogenous precursor synthesis over the course of culture, reduced transport, reduced galactosyltransferase expression or activity, or for increased sequestration of galactose into N-acetylgalactosamine or of uridine into UDP-GlcNAc from increased levels of ammonia (Cayli et al, 1999;Chen and Harcum, 2006;Clark et al, 2005;Gawlitzek et al, 1999;Grammatikos et al, 1998;Pels Rijcken et al, 1995;Ryll et al, 1994;Valley et al, 1999;Wong et al, 2010a,b;Yang and Butler, 2002). In one case, the addition of uridine alone led to increased intracellular pools of UDP-Gal and increased antibody galactosylation (Ryll, 2003 US Patent Application 20030211573).…”
Section: Options For More Specifically Impacting Galactosylationmentioning
confidence: 99%
“…These methods can be divided into several general approaches involving the use of labeling techniques. General labeling methods, such as the use of 2 H 2 O, 18 O, 15 N or 13 C to label the whole organism, were used to show de novo synthesis, as indicated by an increase in the density of the resulting proteins (Gonzalez-Prieto et al, 1995;Gawlitzek et al, 1999;Yao et al, 2001;Goshe and Smith, 2003;Cargile et al, 2004;Roessner-Tunali et al, 2004;Busch et al, 2006;Belloto et al, 2007;Schaff et al, 2008;Zhao et al, 2009). Specific isotopically-labeled (radioactive or stable isotope) amino acids have been used to label cellular proteins, with labeling rates reflecting de novo synthesis, and the rate of loss monitoring proteolysis (Cooke et al, 1979;Thompson et al, 1989;Ong et al, 2002;Doherty et al, 2005;Krü ger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%